Optometry-led psychotherapy module to overcome anxiety and stress occurring during amblyopia therapy - Jyoti Gangta; Renu Thakur; Pinaz Nasim (Journal of Clinical Ophthalmology and Research)
Background: Amblyopia is a vision development disorder that usually manifests during infancy or early childhood. Stress and anxiety often occur in children with amblyopia, highlighting the importance of grasping the relationship between these factors for effective care. Aim: The primary goal of this research was to create a psychotherapy program led by optometrists to address the anxiety and stress due to amblyopia treatment. Methodology: This cohort study examines how integrating psychotherapy with traditional amblyopia therapy impacts patient adherence and visual outcomes. Questionnaire Stress and Anxiety in Pubescent with Amblyopia-16 (SAPA-16), focusing on stress and anxiety among pubescent individuals with amblyopia, was carefully developed and successfully validated. A novel module that merges optometry and psychotherapy was created and tested on 44 pubescent diagnosed with amblyopia. Results: The findings reveal notable enhancements in both visual acuity and stereopsis in patients who underwent amblyopia therapy and psychotherapy. The SAPA 16 scores revealed a notable decrease in stress levels following the intervention. The average score dropped from around 6.0 before the stress test to 4.0 after the stress test, with nonoverlapping confidence intervals confirming the statistical significance of this decline. This emphasizes the significance of combining psychological support with Amblyopia therapy. Conclusion: The therapy efficiently decreases variations in visual parameters, elevating all patients to comparable and enhanced levels after treatment.